The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.4103/gmit.gmit_59_18
|View full text |Cite
|
Sign up to set email alerts
|

Is it the time for laparoscopic management of early-stage ovarian malignancies?

Abstract: The laparoscopic management of early-stage ovarian cancer remains controversial. Some surgeons hesitate to perform laparoscopic staging due to concern with the adequacy of staging, the possibility of tumor spillage and risk of port-site metastasis. Previous studies and literature reviews have reinforced the argument and supported the use of laparoscopy. However, the results were drawn with limited sample size obtained from case-series and case–control studies which result in difficult to make definite conclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…The main factor influenced intraperitoneal spillage might be the size of tumor. Larger tumors might be more likely to rupture [ 24 ]. The studies included in this study did not reported the information about intraperitoneal spillage.…”
Section: Discussionmentioning
confidence: 99%
“…The main factor influenced intraperitoneal spillage might be the size of tumor. Larger tumors might be more likely to rupture [ 24 ]. The studies included in this study did not reported the information about intraperitoneal spillage.…”
Section: Discussionmentioning
confidence: 99%
“… 18 Second, MIS may cause intraoperative cancer cell spillage, leading to peritoneal dissemination or port-site metastasis. 19–21 Third, we still do not know if carbon dioxide (CO 2 ) pneumoperitoneum changes the tumor environment or the biological behavior of tumor cells; thus, promoting tumor spread or metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…18 Second, MIS may cause intraoperative cancer cell spillage, leading to peritoneal dissemination or port-site metastasis. [19][20][21] Third, we still do not know if carbon dioxide (CO 2 ) pneumoperitoneum changes the tumor environment or the biological behavior of tumor cells; thus, promoting tumor spread or metastasis. We found no survival differences, when we reviewed previous studies comparing the survival of patients with early-stage ovarian cancer between laparoscopic and open surgery groups; however, the study designs or the included patients differed in the studies.…”
Section: Discussionmentioning
confidence: 99%
“…Its long-term sequelae, such as lymphedema caused by lymphadenectomy, manifest in over 30% of the patients, and negatively influence the quality of life [40,41]. A laparoscopic approach could reduce some of the surgical morbidity, though further trials would be required before a definitive statement can be made about the clinical value of laparoscopic staging [42][43][44].…”
Section: Discussionmentioning
confidence: 99%